(untitled) (Bangladesh Journal of Medical Science, 2026)
Rhino-cerebral mucormycosis is a rare and rapidly progressing angio-invasive infection affecting immunocompromised individuals, with an extensive surgical resection of the affected bone resulting in a huge defect. Rehabilitation of such surgical defects requires bone augmentation and extended rehabilitation time, with donor site morbidity and inconsistent graft resorption rates. Patient-specific eposteal implants (PSEI) are an alternative approach that can circumvent the shortcomings mentioned above with accuracy and reduced operating time. Quad-zygoma implantssupported prosthesis and removable obturators with cast-partial framework are the other rehabilitation methods in the literature. PSEIs shall be the choice where inadequate zygomatic bone restricts the endosteal zygomatic implant placements. The presented patient suffered from speech disarticulation, dysphagia, food and fluid reflux, and hypernasal twang. The present case report describes the prosthetic rehabilitation of a post-rhino-cerebral mucormycotic surgical defect with a PSEI-supported removable hollow bulb obturator with a 12-month post-prosthetic follow-up. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S184-S187